Artificial Intelligent in the Development of Islamic Education Learning in the Digital Age: A Literature Review Analysis - Zahrotul Luqmi, Fitra; Siti Patimah; Agus Pahrudin; Vina Rohmatika, Ratu (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
In the digital era, PAI learning faces challenges in adapting to technological developments and the needs of students who are digital natives. AI offers innovative solutions to increase the effectiveness and efficiency of PAI learning. The research method used is systematic literature review analysis using a dimensions scientific publication database. In this research, data was found from the dimensions database with the keywords Artificial Intelligence OR Educational Development OR Islamic Religious Education, a total of 16 articles. Data management was then adjusted to QR with the result that 14 articles passed verification according to RQ and 3 articles did not comply with a different discussion topic, then these 14 articles continued at the analysis stage and relevant results were obtained. To provide broader article results, a search was added using Publish or Perish found in Scopus, Google Scholar and Pubmed. The research results show that AI can be integrated in various aspects of learning, one of which is PAI learning which is able to provide comprehensive alternatives, as well as in the integration of artificial intelligence by providing various benefits such as adaptive learning, interactive learning media, and automatic assessment systems. Apart from that, AI also provides many benefits in the world of education, then the challenges, strategies and obstacles encountered in implementing AI in PAI learning also face challenges such as ethical issues, data privacy and information security.